=11m-3n-3s

Simple and best practice solution for =11m-3n-3s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =11m-3n-3s equation:


Simplifying
0 = 11m + -3n + -3s

Solving
0 = 11m + -3n + -3s

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11m' to each side of the equation.
0 + -11m = 11m + -3n + -11m + -3s
Remove the zero:
-11m = 11m + -3n + -11m + -3s

Reorder the terms:
-11m = 11m + -11m + -3n + -3s

Combine like terms: 11m + -11m = 0
-11m = 0 + -3n + -3s
-11m = -3n + -3s

Divide each side by '-11'.
m = 0.2727272727n + 0.2727272727s

Simplifying
m = 0.2727272727n + 0.2727272727s

See similar equations:

| 2x^2-8+3=0 | | 12x-1+2x=x+1 | | -12+27x=-12 | | 10x+10x=118+x | | -3x^2-8x+35=0 | | 1x^2-5x-12=0 | | 5-2x=3x-50 | | 1/3(10x-5)=8 | | 12x=-9-4x^2 | | 1x^2+5x-10=0 | | 20x^2-66x-14=0 | | 1x^2+1x-30=0 | | 2x+1=4.5 | | x+(x+1)=156 | | -7x+7x=+1 | | 6n+6=72 | | 8+x/6=-10 | | 3(y-3)=-2y+6 | | -2x+1=-19+2x | | a^2=9a+36 | | 9/r=3/5 | | 8y-25=2(4y+3) | | 3/8=w/4 | | 27x-9=15 | | 10x-3=7x | | 5x-59=2x-5 | | -16t+116t+101=0 | | 4+3x=x+28 | | 142-3x=33x+22 | | 4(4x+6)=3(2x+18) | | 4+5n=9 | | (w+1)(w+4)= |

Equations solver categories